PENDAMPINGAN MANAJEMEN PRODUKSI RENGGINANG HOME INDUSTRI IBU ENI KECAMATAN METRO TIMUR KOTA METRO - evi meidasari (ANDASIH Jurnal Pengabdian kepada Masyarakat, 2024)
ABSTRACTÂ The development of the modern world creates great pressure on business actors today, including Micro, Small and Medium Enterprises (MSMEs). Rapid changes in technology, culture and contemporary food compared to traditional snacks create high market competition. This has an impact on the competitiveness of MSMEs which have limitations in production management. Limited knowledge regarding the development of the modern world means that MSMEs producing processed rengginang are increasingly limited amidst intense competition. The implementation of this community service targets one of the MSME business actors who feel this impact, namely Mrs. Eni's Rengginang home industry business in East Metro, Metro City. For this reason, Rengginang production management was created to make it easier for producers to administer bookkeeping as a business, increase quality production results and have attractiveness, efficiency and ease for consumers to find Rengginang products.Â Keywords: Rengginang, traditional snacks, production management